2018
DOI: 10.4103/ajps.ajps_120_16
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcome of treatment of jejunoileal atresia in Nigeria

Abstract: Background: Intestinal atresia is a common cause of neonatal intestinal obstruction. Previous reports from Nigeria have indicated a high mortality rate. This is a report of current outcome review from one tertiary center. Patients and Methods: A retrospective analysis of infants managed for jejunoileal atresia in 10 years (2005–2014). The information retrieved from patients’ records was analyzed using SPSS 17. Results: There were 38 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…7,15 Vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, and limb abnormalities (VACTREL) anomalies are known in neonates with intestinal obstruction and contribute to increased morbidity and mortality in these neonates. 9,11,13,14 The complications observed in our study (Table 3) are comaprable to other international studies and Indian studies. 9,[11][12][13][14] A comparatively higher mortality rates are observed from studies reported from low-middle income countries.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…7,15 Vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, and limb abnormalities (VACTREL) anomalies are known in neonates with intestinal obstruction and contribute to increased morbidity and mortality in these neonates. 9,11,13,14 The complications observed in our study (Table 3) are comaprable to other international studies and Indian studies. 9,[11][12][13][14] A comparatively higher mortality rates are observed from studies reported from low-middle income countries.…”
Section: Discussionsupporting
confidence: 87%
“…9,11,13,14 The complications observed in our study (Table 3) are comaprable to other international studies and Indian studies. 9,[11][12][13][14] A comparatively higher mortality rates are observed from studies reported from low-middle income countries. 5 Some causes for this high mortality are prematurity, late presentation, associated congenital anomalies, complications of surgery as well as lack of intensive care facilities.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations